Cooperatives and crisis: economic dynamics in Italian context. (17th June 2019) - Fusco, Floriana; Migliaccio, Guido
This paper focuses on the situation in Italy with specific reference to cooperatives. It aims to analyse their economic situation - represented by two profitability ratios (ROI, ROE) - during the decade 2004-2013. It aims to tests the impact of crisis, geographical area and belonging business sector. Starting from secondary data on AIDA database (at the end 1, 446 cooperatives), the trend analysis and analysis of variance (ANOVA) have been used. The findings show, first of all, that the profitability of cooperatives strongly affected by crisis. Secondly, only the business sector affects the level of profitability. The analysis is interesting because the income has a special meaning in cooperatives: it should, in fact, be added to benefiting members that are accounted for as 'peculiar' management costs.